Mobile Library Services: Best Practices - Harmon, Charles; Messina, Michael (Rowman & Littlefield Publishers, 2013)
Just as Andrew Carnegie’s support changed the landscape of public libraries in America, Apple’s launch of the iPhone on June 29, 2007 forever altered how people expected to interact with services. Libraries, like every other kind of organization, must now make their services—not just their catalogs—available on an array of mobile devices. Mobile Library Servicesprovides 11 proven ways to reach out to mobile users and increase your library’s relevance to their day-to-day lives. Librarians detail how they created mobile apps to how they went mobile on a shoestring budget. Written by public, academic, and special librarians, these 11 best practices offer models for libraries of every type and size.